Diagnostic findings in relatives to victims of sudden unexplained death or non-autopsied possible sudden cardiac death. (25th November 2020) - Dalgaard, C.V; Hansen, B.L; Jacobsen, E.M; Kjerrumgaard, A; Tfelt-Hansen, J; Weeke, P.E; Winkel, B.G; Christensen, A.H; Bundgaard, H
Abstract: Introduction: Sudden cardiac death (SCD) may be caused by several inherited cardiac diseases and screening and treatment of relatives may be lifesaving. Sudden unexplained death (SUD) victims have been autopsied, whereas non-autopsied possible SCD (pSCD) victims are only filtered on manner of death and medical records. Screening of relatives may identify an inherited cardiac disease. Purpose: To assess the diagnostic yield at initial evaluation and during follow-up of relatives to SUD and pSCD victims. Furthermore, to evaluate the outcome in the relatives. Methods: We retrospectively included first-degree relatives to SUD and pSCD victims referred to our tertiary center from 2005 to 2018. Probands with known antemortem inherited cardiac disease were excluded. Data from systematic screening and routine follow-up of the relatives were registered. Results: We included 371 first-degree relatives from 187 families: 276 SUD relatives (age at initial evaluation 35±17 years, 54% men;) and 95 pSCD relatives (age at initial evaluation 40±15 years, 51% men). The diagnostic yield among SUD families was 18%, among pSCD families 13% (p>0.05 between groups). The diagnoses in SUD families were mainly channelopathies (68%), whereas the pSCD families were diagnosed with cardiomyopathies, channelopathies, and premature ischemic heart disease (Figure 1). The vast majority of diagnosed families (93%) were diagnosed at the initial evaluation and only two families were diagnosed during the mean follow-up of 5.4 years. During follow-up, 57 (15%) relatives had a cardiac-related hospitalization, 12 (3%) relatives had a cardiac device implanted, three (1%) relatives died of non-cardiac causes, and one (0.5%) relative had a myocardial infarction. There was no significant difference in cardiac event rates between the SUD and pSCD groups (all p>0.05). Conclusion: One in 6–7 families with SUD or pSCD victims obtained a diagnosis based on screening of relatives; we mainly diagnosed channelopathies in SUD families and a broader spectrum of inherited cardiac disease in the pSCD families. The majority of affected relatives was diagnosed at the initial evaluation and clinical follow-up may not be warranted in all relatives with normal findings at initial screening. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): The Capital Regions Research Foundation and The A.P. Moeller Foundation.